FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PRODUK BARU - Sri Vandayuli Riorini (Universitas Trisakti, 2007)
To be successful in the market, a company should continuously performs product development. However, quality of a new product has been known to have a very big impact on the success of that new product in the market and profitability of a new product. The quality of a new product is affected by contextual influences. The objectiveof this research is to find out the affecting contextual factors on quality of a new product. Data were gathered from 30 employess and 30 consumers in Jakarta by using a simple regression method. The results showed that.(1) quality of a new product is positively affected by customer’ influence and quality orientation,(2) quality of a new product has no effect by its innovation from the company point of view, (3) time pressure has no effect at all on quality of a new product.